2003
DOI: 10.1038/nm956
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific Pparg deletion causes insulin resistance

Abstract: Thiazolidinediones (TZDs) are insulin-sensitizing drugs and are potent agonists of the nuclear peroxisome proliferator-activated receptor-gamma (PPAR-gamma). Although muscle is the major organ responsible for insulin-stimulated glucose disposal, PPAR-gamma is more highly expressed in adipose tissue than in muscle. To address this issue, we used the Cre-loxP system to knock out Pparg, the gene encoding PPAR-gamma, in mouse skeletal muscle. As early as 4 months of age, mice with targeted disruption of PPAR-gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
361
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(378 citation statements)
references
References 45 publications
13
361
1
3
Order By: Relevance
“…Using the Cre-Lox-P-mediated gene targeting, two recent reports described the generation of mice specifically lacking PPARg in muscle and showed that this deletion leads to secondary insulin resistance in the liver and adipose tissue. 18,19 Treatment of this mouse model with troglitazone did not improve skeletal muscle insulin resistance but ameliorated hepatic and adipose insulin sensitivity, supporting the idea that muscle cells directly respond to PPARg agonist treatment, but that local PPARg in muscle is not an essential contributor to systemic antidiabetic effect of TZDs. Ablation of PPARg in mature adipocytes results in improvements of hepatic insulin sensitivity in response to TZD treatment, but did not lower serum triglycerides and free fatty acids.…”
Section: Pparc Is the Primary Target Transcription Factor For Tzdssupporting
confidence: 52%
“…Using the Cre-Lox-P-mediated gene targeting, two recent reports described the generation of mice specifically lacking PPARg in muscle and showed that this deletion leads to secondary insulin resistance in the liver and adipose tissue. 18,19 Treatment of this mouse model with troglitazone did not improve skeletal muscle insulin resistance but ameliorated hepatic and adipose insulin sensitivity, supporting the idea that muscle cells directly respond to PPARg agonist treatment, but that local PPARg in muscle is not an essential contributor to systemic antidiabetic effect of TZDs. Ablation of PPARg in mature adipocytes results in improvements of hepatic insulin sensitivity in response to TZD treatment, but did not lower serum triglycerides and free fatty acids.…”
Section: Pparc Is the Primary Target Transcription Factor For Tzdssupporting
confidence: 52%
“…The question of whether TZDs exert direct effects in muscle and liver has been controversial. In the case of muscle, it has been elegantly addressed by two recent studies of metabolic responses in muscle-specific PPARγ knock-out mouse models [4,32]. There are significant differences between these two models.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, TZDs activate peroxisome proliferator-activated receptor (PPAR) γ, a transcription factor predominantly expressed in adipocytes. While there is some evidence that PPARγ plays a functional role in skeletal muscle [4], its expression levels in muscle and liver are extremely low compared with adipocytes. Secondly, TZDs lower circulating levels of lipids and lipid accumulation in non-adipose tissues including skeletal and cardiac muscle, liver and pancreatic islets [2,5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear receptor for thiazolidinedione, peroxisome proliferator-activated receptor (PPAR) γ, is highly expressed in adipocytes suggesting that thiazolidinediones mainly exert their insulin-sensitising effect through the adipose tissue although controversial results have been published [1,2]. Thiazolidinediones improve insulin sensitivity both in man and in different animal models of insulin resistance [3,4].…”
Section: Introductionmentioning
confidence: 99%